Efeito da adição de CGTase e β-ciclodextrina na qualidade e taxa de envelhecimento de pães - Gonçalves, Ana Karla Rebes [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The present study aimed to investigate the effect of CGTase and βCD on the rheological properties of the wheat flour, and quality and staling rate of the bread. The farinographic, extensographic, pasting, and thermal properties of the flour without (control) and with different concentrations of CGTase (0, 5, 10 and 20 U) or βCD (0, 0.25, 0.5, 1.0 % m/m) were analyzed. Breads were produced with and without βCD or CGTase and their specific volume were determined by seed displacement. Breads were stored at 5 °C for 15 days and during this period were evaluated for moisture and water activity, firmness, retrogradation, color and X-ray diffraction. The water absorption of the flour containing 5 and 10U CGTase increased from 56.5 to 59 %. The elasticity, development time and stability increased while the mixing tolerance index (ITM) reduced for flour containing CGTase, as compared to control. The addition of 5 and 10U of CGTase increased setback and reduced final viscosity whereas the presence of 20U CGTase reduced the peak and final viscosities and setback. The range of the gelatinization temperature (ΔT) of the starch present in the flour (13.15 °C) and enthalpy change (ΔH) were reduced in the presence of CGTase. The specific volume of bread increased 11 % when 5U CGTase was used. The addition of CGTase significantly increased crumb moisture of the fresh bread and improved water retention of the bread crumb until the seventh day of storage. The firmness and ΔH of the bread crumb gradually increased for all samples during storage, but the addition of 5U CGTase reduced the ΔH until the 3rd day of storage and reduced 40% of the firmness when compared to the control. The water absorption, development time and stability were not affected by the addition of 0.25 and 0.5 % βCD. However, the presence of 1.0 % βCD increased water absorption and reduced development time and stability of the flour. The ITM increased for samples containing ...

Neste estudo o efeito da CGTase e da βCD nas características reológicas da farinha, na qualidade e no processo de envelhecimento do pão foi investigado. As propriedades farinográficas, extensográficas, viscográficas e térmicas na presença de diferentes concentrações de CGTase (0, 5, 10 e 20 U) e de βCD (0, 0,25, 0,5, 1,0 %) foram analisadas. Pães foram produzidos sem e com CGTase ou βCD e seu volume específico determinado por deslocamento de sementes. Os pães foram armazenados a 5 ºC por 15 dias e neste período foram avaliados quanto à umidade, atividade de água, firmeza, retrogradação, cor e difracção de raios-X. A absorção de água da farinha contendo 5U e 10U de CGTase aumentou de 56,5 para 59 %. A elasticidade, o tempo de desenvolvimento e a estabilidade aumentaram, enquanto o índice de tolerância à mistura (ITM) reduziu para todas as amostras contendo CGTase, quando comparadas ao controle. A adição de 5 e 10U de CGTase aumentou o setback e reduziu a viscosidade final, enquanto que a presença de 20U de CGTase reduziu as viscosidades de pico e final e o setback. A faixa de temperatura de gelatinização (ΔT) do amido presente na farinha de trigo (13,15 oC) e a variação de entalpia (ΔH) foram reduzidas na presença de CGTase, independente da concentração utilizada. O volume específico do pão aumentou 11 % quando 5U de CGTase foi utilizada. A adição de CGTase aumentou significativamente a umidade do miolo dos pães frescos e melhorou a retenção de água do miolo dos pães até o sétimo dia de armazenamento. A firmeza e o ΔH do miolo aumentaram gradualmente para todas as amostras durante o armazenamento, mas a adição de 5U de CGTase reduziu o ΔH até o 3º dia de armazenamento e reduziu a firmeza dos pães frescos em 40 %, quando comparados ao controle. A absorção de água, os tempos de desenvolvimento e de estabilidade não foram afetados pela adição de 0,25 e 0,5 % de βCD. No entanto, ...
Keywords: Tecnologia de alimentos; Pão - Armazenamento; Alimentos - Conservação; Beta-Ciclodextrinas; Food technology